1989
DOI: 10.1149/1.2096580
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Deposited Silicon Nitride for Indium Phosphide Encapsulation

Abstract: The composition and annealing characteristics of plasma deposited silicon nitride encapsulating films on ion implanted indium phosphide have been investigate d . X-ray photoelectron spectroscopy was employed to study the surface of InP substrates cleaned with organic solvents and HF or HIO3 solutions prior to encapsulation. The composition of silicon nitride films deposited with 13.56 MHz RF excitation was determined through Auger electron spectroscopy and infrared spectroscopy both before and after annealing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Low temperature dielectric film growth may also be desired in silicon processing schemes where thermal budgeting is a major consideration. Plasma-enhanced chemical vapor deposition (PECVD) (1)(2)(3)(4), remote plasma-enhanced chemical vapor deposition (RPECVD) (5)(6)(7)(8)(9), photochemical vapor deposition (PVD) (10), and electron cyclotron resonance (ECR) microwave plasma-enhanced chemical vapor deposition (MPECVD) (11)(12) all employ energy inputs that stimulate the nonthermal production of reactive intermediates from the initial feed reactants. These reactive intermediates, which can consist of excited molecules, atoms, and radicals, then react to form the dielectric films on substrates maintained at low temperatures.…”
mentioning
confidence: 99%
“…Low temperature dielectric film growth may also be desired in silicon processing schemes where thermal budgeting is a major consideration. Plasma-enhanced chemical vapor deposition (PECVD) (1)(2)(3)(4), remote plasma-enhanced chemical vapor deposition (RPECVD) (5)(6)(7)(8)(9), photochemical vapor deposition (PVD) (10), and electron cyclotron resonance (ECR) microwave plasma-enhanced chemical vapor deposition (MPECVD) (11)(12) all employ energy inputs that stimulate the nonthermal production of reactive intermediates from the initial feed reactants. These reactive intermediates, which can consist of excited molecules, atoms, and radicals, then react to form the dielectric films on substrates maintained at low temperatures.…”
mentioning
confidence: 99%
“…Comparing the results obtained for different compositions of BiSrCaCuO material, including different doping/substitution cases, the E a was found to range from 75 to 355 kJ mol −1 [51][52][53]. However, in this work, substitution of gallium, particularly for x = 0.2, 0.8 and 1.0 samples, increased the E a value either by changing the diffusion mechanism within the solubility limit of the BiSrCaCuO material for Ga atoms or by providing a variation in the bonding distance between the BiO-GaO layers.…”
Section: Dta Resultsmentioning
confidence: 94%
“…The 30 min CF4 plasma cleaning was necessary to remove the film deposits on the chamber walls from previous deposition runs. Our previous experiments (17,18) have indicated that 30 min were long enough for the removal of the films from prior runs. Then the substrates were loaded into the chamber immediately after the initial clean to minimize any native oxide growth.…”
Section: Methodsmentioning
confidence: 99%
“…The substrates were initially cleaned according to the following procedure (17). The samples were first degreased and then dipped for 30 s each in solutions of (1:1:4)12:1 (NCl:HF:H20):H20= (solution A) followed by 10% H3PO4 in deionized (DI) H20 (solution B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation